2010
DOI: 10.1002/rcm.4553
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the electrospray ionization behaviour and biological activity of some phosphino Cu(I) complexes

Abstract: Electrospray ionization mass spectrometry was usefully employed for the characterization of three phosphino copper(I) complexes of medicinal interest. This technique revealed that the original [CuL(4)](+) pro-drugs (L = hydrophilic tertiary phosphine) underwent dissociation with production of coordinative unsaturated [CuL(3)](+) and [CuL(2)](+) species, which represented key intermediates for the activation of potential biological properties. The more favoured was the displacement of the ligands from the [CuL(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…In the case of copper, the nature of the coordinated phosphine determined the degree of dissociation of the [Cu(L) 4 ] + complex and the formation of the likely 'active ingredients' [Cu(L) 2 ] + and [Cu(L)] + . Hence, [Cu(thp) 4 ] + 1 was found to be more cytotoxic than [Cu(PTA) 4 ] + 4 [71]. Speciation studies involving silver and gold complexes are in progress.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the case of copper, the nature of the coordinated phosphine determined the degree of dissociation of the [Cu(L) 4 ] + complex and the formation of the likely 'active ingredients' [Cu(L) 2 ] + and [Cu(L)] + . Hence, [Cu(thp) 4 ] + 1 was found to be more cytotoxic than [Cu(PTA) 4 ] + 4 [71]. Speciation studies involving silver and gold complexes are in progress.…”
Section: Discussionmentioning
confidence: 96%
“…As observed in the ESI(+)MS spectra, none of [M(L) 4 ] + species show the molecular ion peak, but the ESI-MS base peak is consistently ascribed to the [M(L) 2 ] + molecular fragment. At micromolar concentrations, typical of both ESI-MS measurements and in vitro cell culture conditions, the easy formation of [Cu(L) 2 ] + and [Cu(L)] + species was found to be the key factor for controlling the biological activity of the native [Cu(L) 4 ] + species [71]. In the case of copper, the nature of the coordinated phosphine determined the degree of dissociation of the [Cu(L) 4 ] + complex and the formation of the likely 'active ingredients' [Cu(L) 2 ] + and [Cu(L)] + .…”
Section: Discussionmentioning
confidence: 97%
“…10 -5 M). 32 The difficulty of growing crystals of complexes 2 and 3 suitable for X-ray diffraction studies and the lack of unambiguous NMR and MS data confirming the [Cu(P)4] + assembly prompted us to investigate the molecular structure at the Cu site in the representative [Cu(DAPTA)4]BF4, 2 by X-Ray Absorption spectroscopy (XAS). XANES spectra of Cu complexes displayed a typical feature in the rising part of the XAS spectrum which is assigned to the 1s-4p electronic transition.…”
Section: Synthesis and Characterization Of Copper(i) Complexesmentioning
confidence: 99%
“…In agreement with this suggestion, ESI-MS experiments showed that the chelate complex (1) retains its tetracoordination at the high dilutions required by in vitro and MS experiments (10 −5 -10 −6 mol L −1 ), while the complexes containing monodentate phosphines, (2) and (3), are partially dissociated. 12,15 Therefore, the nature and stability of the species of these Cu(I)-based compounds seems to be of fundamental importance for their biological activity. In this work, solution equilibria for the formation of Cu(I) and Ag(I) complexes with the phosphine 1,3,5 triaza-7-phosphadamantane (PTA, Scheme 1) are reported.…”
Section: Introductionmentioning
confidence: 99%